Relationship Between Learning Style with Biology Learning Outcomes of Grade X High School Students - Stefi Novia Sapitri; Lisa Deswati; Wince Hendri (Journal of Biology Learning, 2022)
The success or failure of students in the learning process can be seen from the learning outcomes received by students. In this case, educators play an important role in determining student learning outcomes. Educators who know students' learning styles will understand the diversity of students' learning styles in receiving and processing information. This study aims to determine student learning styles and to determine the relationship between student learning styles and biology learning outcomes for class X MIPA students at SMA Negeri 8 Padang. This type of research is quantitative. This research was carried out at SMA Negeri 8 Padang with a total sample of 45 students of class X MIPA in SMA who were registered in the odd semester of the 2021/2022 academic year. The sampling technique was simple random sampling using a questionnaire containing statements consisting of visual, auditory and kinesthetic learning styles. Each statement is 10 so that the total is 30 statements. The results of data analysis on the correlation test of 0.304 have a low correlation, meaning that there is a relationship between student learning styles and biology learning outcomes for class X MIPA students at SMA Negeri 8 Padang. The results of the t-test obtained t-test results of 2.048 indicating that there is a significant relationship. The result of the coefficient of determination of learning style is 55%, which means that learning style (X) contributes to students' biology learning outcomes (Y).